A Glimpse Into the Structure and Function of Atypical Type I Chaperonins - Ansari, Mohammed Y.; Mande, Shekhar C. (Frontiers in Molecular Biosciences, 2018)
Chaperonins are a subclass of molecular chaperones that assist cellular proteins to fold and assemble into their native shape. Much work has been done on Type I chaperonins, which has elucidated their elegant mechanism. Some debate remains about the details in these mechanisms, but nonetheless the roles of these in helping protein folding have been understood in great depth. In this review we discuss the known functions of atypical Type I chaperonins, highlighting evolutionary aspects that might lead chaperonins to perform alternate functions.